Surfactant Evaluation and Static Adsorption at High Temperature Reservoir using Seawater Salinity Surfactant Flooding Application. - ZULKIFLI, NAZLIAH NAZMA (2021)
Surfactant flooding is an established technology applied to produce residual oil. This research addresses two concern areas for surfactant flooding performance under challenging conditions. Conventional surfactants, such as sulfates and sulfonates based, can hydrolyze at high temperatures and precipitate in seawater respectively, therefore unique surfactant formulations are required. The first objective was achieved by screening the commercially available surfactants for field conditions of 106°C under seawater injection. The screening was carried out by analyzing the surfactant solubility, phase behavior, interfacial tension (IFT), and thermal stability and it showed that a blend of alkyl ether carboxylate (AEC) and alkyl polyglucoside (APG) mixed with a mass ratio of 50:50 was a unique formulation for this condition. The surfactant screening tests were done in anaerobic conditions to avoid oxygen presence in the system. The study's second objective was to perform a comprehensive assessment of the surfactant system’s static adsorption at high temperature under the influence of various factors such as clay content, clay mineralogy, surfactant concentration and brine salinity. Findings showed that total surfactant adsorption increases as the clay content is higher and the highest is in illite-smectite, followed by illite and lowest for kaolinite, due to the high surface area and CEC in clays. Surfactant adsorption slightly decreases as temperature increases from 80°C to 120°C due to the weaker physical bonding between the surfactant and rock surfaces at high temperatures. Concerning the concentration effect, as the surfactant concentration increases, total surfactant loss due to adsorption increases and the surfactant isotherms obey the specific adsorption region. Experiment using DOE model was executed to validate the OFAT results and the model provides the relationship between surfactant adsorption with temperature, salinity and clay content. This research successfully recommended a workable surfactant formulation that can survive challenging conditions (106°C and seawater salinity) and determine its adsorption capacity at high-temperature surfactant flooding.